PEMAHAMAN PELAYAN TENTANG KARUNIA BAHASA ROH - Ardian Tuhumury; Gidion Gidion; Gregorius Suwito (JOURNAL of THEOLOGICAL STUDENTS, 2022)
Based on the results of temporary observations, the researchers found that the understanding of the ministers about the gift of tongues in GBT Kristus Raja Ternate was not optimal. This is based on observations and interviews with the congregation and church leaders. So the aim is to find out what the ministers understand about the gift of tongues in the Bethel Tabernacle Church of Christ the King of Ternate. In this study, the researcher used a qualitative research method. Based on the results of testing qualitative data on five indicators, it can be concluded that the Minister's understanding of the gift of tongues in GBT Kristus Raja Ternate is good.